2023
DOI: 10.21203/rs.3.rs-2430661/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Construction and application of sponge city resilience evaluation system: A case study in Xi 'an, China

Abstract: Urban vulnerability is evident when highly complex flood risks overlap with diverse cities, and it is important to enhance the resilience of cities to flood shocks. In this study, a sponge city resilience assessment system is established considering engineering, environmental and social indicators, and the grey relational analysis method(GRA) is used to quantify sponge city resilience. At the same time, a multi-objective optimization model is established based on the three dimensions of water ecological enviro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…According to the Jiaozuo Sponge City Standard Construction Three-Year Implementation Plan, the sponge city construction of Jiaozuo involves 151 projects in 7 categories, with a total investment of 4.233 billion yuan. After the sponge city was built, according to the water quality test results, the water quality of the original 10 black and smelly water bodies in Jiancheng District of Jiaozuo City basically reached the standard after treatment, and there was no black and smelly water [11]. Moreover, the public opinion poll showed that the surrounding residents were satisfied with the water bodies' treatment outcomes, and there was no event that led to a complaint being filed.…”
Section: Results Of Pilot Cities: a Case Study Of Jiaozuo City In Hen...mentioning
confidence: 99%
See 4 more Smart Citations
“…According to the Jiaozuo Sponge City Standard Construction Three-Year Implementation Plan, the sponge city construction of Jiaozuo involves 151 projects in 7 categories, with a total investment of 4.233 billion yuan. After the sponge city was built, according to the water quality test results, the water quality of the original 10 black and smelly water bodies in Jiancheng District of Jiaozuo City basically reached the standard after treatment, and there was no black and smelly water [11]. Moreover, the public opinion poll showed that the surrounding residents were satisfied with the water bodies' treatment outcomes, and there was no event that led to a complaint being filed.…”
Section: Results Of Pilot Cities: a Case Study Of Jiaozuo City In Hen...mentioning
confidence: 99%
“…Moreover, the public opinion poll showed that the surrounding residents were satisfied with the water bodies' treatment outcomes, and there was no event that led to a complaint being filed. There has been varied degrees of improvement in each of the four areas of water ecology, water resources, water environment, and water security [11].…”
Section: Results Of Pilot Cities: a Case Study Of Jiaozuo City In Hen...mentioning
confidence: 99%
See 3 more Smart Citations